Analisis Materi Supervisi Tingkat Sekolah Dasar Negeri 080658 (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to analyze the supervision materials implemented at State Elementary School 080658. The primary focus is on the effectiveness of the supervision content in improving teaching quality and teacher professionalism. A qualitative descriptive method was employed, with data collected through observation, interviews, and document analysis. The results show that the supervision materials cover lesson planning, instructional delivery, student assessment, and teacher professional development. Supervision conducted systematically and continuously was found to enhance teachers' pedagogical competence and performance. However, several challenges were identified, such as limited time, lack of training for supervisors, and some teachers’ resistance to supervision. This study recommends improving supervisor capacity through training, developing more contextual supervision materials, and applying a more collaborative supervisory approach to enhance the effectiveness of supervision at State Elementary School 080658.